Short-term costs of alcohol-associated hepatitis care in different clinical settings - Chi Mai Nguyen; Jing Su; Yang Li; Ryan Healey; Shihui Jiang; Jiangqiong Li; Naga Chalasani; Samer Gawrieh; Suthat Liangpunsakul; Wanzhu Tu (Hepatology Communications)
Background:. Alcohol-associated hepatitis (AH) leads to high rates of mortality and health care costs. Understanding the immediate costs after an AH diagnosis and identifying key cost factors is crucial for health care policies and clinical decisions. Objectives:. This study quantifies medical costs within 30 days of an AH diagnosis across outpatient (OP), emergency department (ED), and inpatient (IP) settings. It also explores concurrent diagnoses and their effects on care costs. Methods:. We conducted a retrospective cohort study using deidentified data from Optum’s Clinformatics Data Mart. The cohort included individuals aged 21 years and older diagnosed with AH from January 1, 2016, to September 30, 2023. Patients were categorized by care setting (OP, ED, or IP). Costs were calculated for the 30 days before and after AH diagnosis and adjusted to 2023-dollar values. Comorbidities were identified using Elixhauser comorbidity software, and multivariable linear regression models were used to analyze medical costs. Results:. The cohort included 34,974 individuals diagnosed with AH: 8048 in OP (23%), 2736 in ED (7.8%), and 24,190 in IP (69.2%). Average spending in the 30 days prior to AH diagnosis was $7334 for OP, $5740 for ED, and $14,458 for IP. Following AH diagnosis, average costs rose to $8345 for OP, $20,990 for ED, and $88,655 for IP, reflecting increases of 14%, 266%, and 413%, respectively. Significant cost drivers in IP included comorbidities associated with moderate-to-severe liver disease, metabolic syndrome, liver transplant, and mortality during the 30-day follow-up period. Conclusions:. Immediate costs following an AH diagnosis are substantial, particularly for IP care. Costs increase significantly with high-cost comorbidity clusters and among patients who die, underscoring the need for effective management of comorbidities in AH care.